Influential factors and performance of logistics outsourcing practices: an evidence of malaysian companies - Zailani, S.; Shaharudin, M.R.; Razmi, K.; Iranmanesh, M. (Springer Verlag (Germany), 2017)
Despite the growing trend of logistics outsourcing, there are very limited sources of literature on logistics outsourcing, especially in determining the relationship between factors influencing outsourcing and the extent of logistics outsourcing practices. In this study, we tap into the field of strategic management to help clarify the mechanisms underlying the links between factors influencing, logistics outsourcing practices and outsourcing performance. A model based on the resource based view illustrates the hypothetical connections among these variables. The data gathered from the survey were analysed using SmartPLS software. A response rate of 21 % out of the 486 firms selected was achieved and fixed as the empirical data for this study. The results of this study provide support that superior performance is correlated to the resources of the firm. The analysis shows that lack of human and physical asset capabilities, as well as transaction uncertainty influence the extent of different logistics outsourcing practices. The four logistics outsourcing practices under study were found to have a positive relationship with logistics outsourcing performance, particularly strategic focus. This study shows that although theoretically firms aim at cost reduction by employing a logistics outsourcing strategy but not proven in this study because the financial benefit was only positively contributed by one of the four logistics outsourcing practices under study. Besides that, the results from this study also support that most firms outsource their non-core activities of the logistics practices to respond to the transaction uncertainty that their business experiences.